Are Irrigation Rehabilitation Projects Good for Poor Farmers in Peru? - Datar, Gayatri (2012)
This paper analyzes changes in agricultural production and economic welfare of farmers in rural Peru resulting from a large irrigation infrastructure rehabilitation project. The analysis uses a ten-year district panel and a spatial regression discontinuity approach to measure the causal effect of the intervention. While general impacts are modest, the analysis shows that the project is progressive--poor farmers consistently benefit more than non-poor farmers. Farmers living in districts with a rehabilitated irrigation site experience positive labor dynamics, in terms of income and agricultural jobs. Poor farmers increase their total income by more than $220 per year compared with the control group, while rich farmers do not experience such an income gain. The results also show crop specialization patterns in the economic status of farm households; poorer farm households increase their production of staple crops, such as beans and potatoes, while non-poor beneficiary farmers cultivate more industrial crops. Findings from this evaluation have important implications for pro-poor policy design in the agricultural sector.